The Role of the Acetylcholine System and Its Components in the Development of Post-COVID Syndromes (Review) - Dmitriy V. Muzhenya; Sergey P. Lysenkov (Northern (Arctic) Federal University, 2024)
According to the latest data, COVID-19 is classified as a respiratory virus. However, it has been proven to cause a significant multi-organ dysfunction. Despite the increase in the effectiveness of treatment tactics, a post-COVID-19 symptom complex has been observed in patients after recovery, manifesting itself as cephalalgia, brain fog, high fever, muscle weakness and a decrease (or increase) in arterial pressure. To describe this condition, a clinical characteristic has been proposed: post-acute COVID-19 syndrome (PACS). Approximately 57 % of patients hospitalized with COVID-19 have symptoms of PACS even one year after initial infection with COVID-19. This pathological condition is being actively studied, but the question of the causes of PACS and its development mechanisms remains open. One of the possible reasons behind this symptomatology, in our opinion, is a disorder of the body's acetylcholine system and its components. The acetylcholine system plays an integral role in various physiological and pathophysiological processes, such as the regulation of the muscular system, immune and inflammatory reactions, wound healing, as well as the development of cardiovascular, respiratory and other diseases. A key way of translating acetylcholine signals in the body is through the use of neurotransmission via a chemical synapse. Based on current literature data, there is reason to believe that viral invasion can significantly change the functional activity of the vagus nerve by disrupting signal transmission in a synapse. We believe that the hyperimmune response caused by COVID-19 triggers a chain of pathological mechanisms that are associated with disrupted nitric oxide production and imbalance in acetylcholine and its receptors. An understanding of these processes may open up prospects for improving the effectiveness of treatment and rehabilitation of patients with COVID-19.